2018
DOI: 10.1159/000489370
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation Negatively Regulates CSR1-Dependent Prostate Cancer Cell Death

Abstract: Background/Aims: SUMOylation is a dynamic process and reversed by the activity of SUMOspecific proteases (SENPs) family. SENP1, a member of this family, is highly expressed and plays oncogenic roles in diverse cancers including prostate cancer. However, the SENP1-transgenic mice exhibit aberrant transformation of the mouse prostate gland but do not develop cancer. Cellular Stress Response 1 (CSR1) is a tumor suppressor gene and frequently deleted in prostate cancers. Overexpression of CSR1 in prostate cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Modulating SENP1 level dictates colony formation of prostate cancer cell lines, tumor growth in nude mice and also prostate cancer cell migration and invasion (40). SENP1 interacts with and deSUMOylates CSR1 to prevent its degradation and enhances CSR1-dependent prostate cancer cell death (41). Herein, we present evidence that MT inhibits the proliferation of LNCaP cells by decreasing the expression of SENP1, which is required for the full activation of ARs.…”
Section: Introductionmentioning
confidence: 81%
“…Modulating SENP1 level dictates colony formation of prostate cancer cell lines, tumor growth in nude mice and also prostate cancer cell migration and invasion (40). SENP1 interacts with and deSUMOylates CSR1 to prevent its degradation and enhances CSR1-dependent prostate cancer cell death (41). Herein, we present evidence that MT inhibits the proliferation of LNCaP cells by decreasing the expression of SENP1, which is required for the full activation of ARs.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, based on the report that the SCARA3 promoter region is hyper-methylated in prostate cancer [ 13 ], there is a possibility that hyper-methylation is also present in lung cancer. In addition, sumoylation of the K582 region of SCARA3 can reduce protein stability [ 43 ]. Therefore, there is a need to analyze SCARA3 promoter methylation and study sumoylation of SCARA3 protein in lung cancer treatment using SCARA3 expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have shown that mutation of newly identified SUMO modification sites of USP39 further promotes the proliferation-enhancing effect of USP39 on prostate cancer cells. Among the SUMOylated proteins in prostate cancer are the driving proteins such as AR [134,263,[265][266][267][268][269][270], PTEN [271], p53 [216,272], ATF3 [273], FOXA1 [274], FOXA2 [275], CSR1 [276], TBL1 and TBLR1 [277], WWOX [278], pontin [279] SLUG [280], and SNAIL1 [281]. Two SUMOylation residues (K386 and K520) are defined in AR [134].…”
Section: Sumoylationmentioning
confidence: 99%